Keyakinan terhadap Tuhan sebagai Landasan Etika Spiritual dalam Serat Kitab Kalam Qodrat - Anugrah Putri Juniarti (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the values of belief in God as the foundation of spiritual ethics in Serat Kitab Kalam Qodrat (SKKQ), a classical Javanese literary work rich in Sufi teachings. Employing a hermeneutic approach, the research explores the symbolic and theological meanings of key concepts such as tauhid (divine unity), qodrat (divine power), iradat (divine will), iman (faith), ma‘rifat (gnosis), prayer, and remembrance (dhikr). The data is based on the transliterated version by Sulistianingsih (2016). The findings reveal that SKKQ presents tauhid not only as a theological doctrine but also as an ethical guide, promoting surrender (sumeleh) to divine will and encouraging socially grounded spiritual behavior. The Qur’an is also portrayed as a symbol of divine knowledge, emphasizing the text’s role as a medium for transcendence and inner transformation. Thus, SKKQ offers relevant insights into religious moral education and spiritual reflection amid the ethical crisis of modern society.